Factors in the Fight against Corruption in the Context of Civil Society and the Rule of Law - PODOROZHNA, Tetiana S.; VDOVICHEN, Vitalii A.; VAKARIUK, Liudmyla V. (Journal of Advanced Research in Law and Economics, 2019)
The research analyzes the main conditions by having which the state is able to fight against corruption. The preconditions and means of fight against corruption are determined; the results of their implementation in life are considered based on the examples of some countries, namely, availability of effective legislation, political will of the state, specialized bodies of fight against corruption, the establishment of civil society. It is noted that the fight against corruption is the management through a developed network of social institutions created on the basis of ‘participatory democracy’, that is, the interaction of personality, society and state on the principles of social partnership. This concept refers to a complex of political relations and technologies, which establishes public supervision over the activities of state authorities. At the same time, the latter requires a political will to fight against corruption, the legislative provision of this fight and the strict implementation of the adopted legislative acts. The main task for the civil society structures in the fight against corruption is the implementation of public participation in the process of preparing, discussing, adopting and monitoring the implementation of power decisions. Corruption as a systemic problem in Ukraine, demoralizing society, generates such a negative phenomenon of legal consciousness as legal nihilism in the social environment.